COVID-19 pandemic and lockdown increase the frequency and severity of periorbital dog bite injuries in children - Poramate Pitak-Arnnop; Prim Auychai; Keskanya Subbalekha; Nattapong Sirintawat; Chatpong Tangmanee; Jean-Paul Meningaud; Robert Messer-Peti; Andreas Neff (Elsevier, 2022)
Objective: To determine whether the COVID-19 pandemic and lockdown increase the risk of head, neck, and face (HNF) dog bite injuries in children. Methods: Using a retrospective cohort study design, the investigators enrolled a sample of children presenting with HNF dog bite injuries during 22 weeks before and 22 weeks during the COVID-19 pandemic in a German level 1 trauma center. The predictor variables were COVID-19 pandemic and lockdown. The outcome variables were grouped into demographic, anatomic, injury-related, and therapeutic. Appropriate statistics were computed, and statistical significance was set at P ≤ .05. Results: The sample included 36 subjects (19.4% girls; 97.2% Caucasians; 50% isolated periorbital injuries; 61.1% during the lockdown; 16.7% after the lockdown) with an average age of 8 ± 3.3 years. Compared to the pre-COVID-19 period, pediatric HNF dog bite injuries increased ca. 5.5- and 1.5-fold during and after the lockdown, respectively. The COVID-19 pandemic was significantly associated with severe household injury from a pet dog, number of inpatients and treatments in the operating room, and prolonged hospitalization. Isolated periorbital injury was common during the COVID-19 pandemic (P = 0.04; relative risk [RR], 4.86; 95% confidence interval [95% CI], 0.76 to 31.12), especially during the lockdown (P = 0.02; RR, 4.36; 95% CI, 0.72 to 26.6). Conclusion: During the COVID-19 pandemic, especially during the lockdown, there is an increasing tendency of frequency and severity of domestic HNF dog injuries in children, and periorbital region is the most injury-prone.